Integration of QTL Mapping and Gene Fishing Techniques to Dissect the Multi-Main Stem Trait in Rapeseed (Brassica napus L.) - Zhao, Weiguo; Chao, Hongbo; Zhang, Lina; Ta, Na; Zhao, Yajun; Li, Baojun; Zhang, Kai; Guan, Zhoubo; Hou, Dalin; Chen, Kang; Li, Huaixin; Zhang, Libin; et al. (Frontiers in Plant Science, 2019)
Rapeseed is one of the most important oilseed crops in the world. Improving the production of rapeseed is beneficial to relieve the shortage of edible vegetable oil. As the organ of support and transport, the main stem of rapeseed controls the plant architecture, transports the water and nutrients and determines the number of inflorescence. Increasing the number of main stems would be helpful for the yield improvement in Brassica napus (B. napus). This attractive multi-main stem (MMS) trait was observed in the KN DH population. We not only investigated the frequency of MMS traits, but also dissected the genetic basis with QTL mapping analysis and Gene-Fishing technique. A total of 43 QTLs were identified for MMS based on high density linkage map, which explained 2.95-14.9% of the phenotypic variation, among which two environmental stable QTLs (cqMMS.A3-2 and cqMMS.C3-5) were identified in winter and semi-winter environments. Epistatic interaction analysis indicated cqMMS.C3-5 was an important loci for MMS. According to the functional annotation, 159 candidate genes within QTL confidence intervals, corresponding to 148 Arabidopsis thaliana (A. thaliana) homologous genes, were identified, which regulated lateral bud development and tiller of stem, such as shoot meristemless (STM), WUSCHEL regulated related genes, cytokinin response factors (CRF5), cytokinin oxidase (CKX4), gibberellin-regulated (RDK1), auxin-regulated gene (ARL, IAR4) and auxin mediated signaling gene (STV1). Based on Gene-Fishing analysis between the natural plants and the double main stem (DMS) plant, 31 differentially expressed genes (DEGs) were also obtained, which were related to differentiation and formation of lateral buds, biotic stimulus, defense response, drought and salt stress responses, as well as cold response functional genes. In addition, by combining the candidate genes in QTL regions with the DEGs that were obtained by Gene-Fishing technique, six common candidate genes (RPT2A, HLR, CRK, LRR-RLK, AGL79 and TCTP) were identified, which might probably be related to the formation of MMS phenotype. The present results not only would give a new insight into the genetic basis underlying the regulation of MMS, but also would provide clues for plant architecture breeding in rapeseed.